Interaktion og iscenesættelse - Thygesen, Mads (Peripeti, 2021)
Thygesen conducts a critical examination of the notion of interaction in (contemporary) theatre through an examination of the terms ‘staging’ and ‘performance’. The terms, Thygesen argues, originate from two separate historic and analytic discourses and must consequently be exponents for two different perspectives on how to view, understand and respond to theatre.